Bureaucratic Innovation : Accelerating Public Services as an Implementation of Agile Governance in Southwest Papua - Alfonsina Djitmau; Dian Ferriswara; Sapto Pramono; Sri Kamariyah (Lembaga Pengembangan Kinerja Dosen, 2025)
In the era of digital transformation, public bureaucracies face increasingly complex demands to become more adaptive, responsive, and efficient in meeting evolving public expectations. This change is increasingly crucial in newly autonomous regions such as Southwest Papua Province, which are building their governance systems from scratch. This research aims to examine the implementation of Agile Governance in accelerating public services, specifically by examining the extent to which agile principles such as flexibility, cross-actor collaboration, and continuous iteration have been applied within the regional bureaucracy. The research employed a descriptive qualitative approach with a desk study method based on secondary data sourced from policy documents, institutional reports, relevant regulations, and the latest scientific literature. Data analysis was conducted using content analysis techniques to identify themes, patterns, and gaps in policy implementation. The results indicate that the implementation of Agile Governance in Southwest Papua remains limited, partial, and has not been systematically integrated into the regional bureaucratic framework. Current efforts to digitize public services emphasize technical aspects, but are not supported by adequate regulations, robust digital infrastructure, or strengthened human resource capacity. This results in the implementation of agile principles such as transparency, adaptability, and collaboration not being fully reflected in bureaucratic practices. This study concludes that the successful implementation of Agile Governance requires comprehensive institutional transformation, increased adaptive capacity of the apparatus, and contextualized governance design tailored to the needs of the new autonomous region. The study's contribution is to provide an empirical and conceptual foundation for promoting bureaucratic reform in Southwest Papua while enriching academic literature in the field of adaptive public administration, particularly within the framework of digital and agile governance.